Evaluation of a sex hormone-binding globulin automated chemiluminescent assay. (September 2013) - Dittadi, Ruggero; Fabricio, Aline S. C.; Michilin, Silvia; Gion, Massimo
Abstract: Background . Sex hormone-binding globulin (SHBG) is the main transport protein of sex steroids. This study evaluated the analytical performance of the recently developed Access SHBG assay (Beckman Coulter) and compared it with other commercial methods for the determination of serum SHBG. Clinical validation was also performed. Methods . Analytical performance including within-run and between-run imprecision was assessed for Access SHBG assay on the automated Beckman UniCel DxI800 analyzer. Linearity was assessed using five dilutions of the serum samples. For methods comparison, SHBG levels were determined also with Immulite 2000 analyzer (Siemens Healthcare) using clinical serum samples ( n = 104). For clinical validation 135 specimens from healthy subjects, pregnant women, hypothyroid and hyperthyroid patients were analyzed. Results . Total coefficients of variation were < 5.5%. Linearity test showed > 90% recovery for all samples and for all dilution rates. Comparison analysis (Bland-Altman difference analysis and Passing-Bablock regression) showed an acceptable agreement between selected methods. SHBG values measured by Access SHBG assay in different groups of subjects were in agreement with other clinical evidence. Conclusions . Automated Access SHBG assay appears to be a reliable and easy to perform assay, as necessary for application in routine diagnostics.